Incorporating Arts-Based Pedagogy: Moving Beyond Traditional Approaches to Teaching Qualitative Research - Moreno, Rhia; Hobgood Guthrie, Kate; Strickland, Katie (Teaching and Learning Inquiry, 2023)
Arts-based pedagogy has the potential to reimagine “traditional” research to engage learners in expanded and innovative methods, while also creating space for student voices. Grounded in a Deweyan experiential framework informed by arts-based pedagogy, this reflective dialogue revolves around a pedagogical reframing of a data analysis unit in a qualitative research course with specific focus on the incorporation of creative analysis. We came together as three participants (instructor, student, and scholar) within this experience to collaboratively share insights on the pedagogical approach, particularly as experienced through the eyes of the learner. Implications include how arts-based experiential inquiry can empower novice researchers to explore new avenues for sense-making while also extending across disciplines to support the inclusion of arts-based reflective practices in higher education. Click here to read the corresponding ISSOTL blog post.